Role Of Pracchan Karma And Samana Chikista In The Management Of Alopecia Areata (Indralupta): A Case Study - Bose, Shreelogna (International Research Journal of Ayurveda & Yoga, 2020)
Hairs are distinct feature of one’s beauty. Its not only boosts up the individual confidence but also increases one’s personality. Everyone desires to have long beautiful hair. But with the advent of faulty dietary habits and sedentary life style, socio economic work load; now a days its leading to premature greying of hair and hair fall related problems etc. Even in our ancient classics both Acharya Susruta and Charaka have mentioned that virudha ahar and vihar leads to manifestation of Khalitya, Palitya, Indralupta, Bali etc. Indralupta is one such hair loss problem which is kept along with khalitya and further kept under kshudra roga and Siro rogas .Here is one case study of a lady who was suffering from Alopecia Areata (Indralupta) for last 1 years. She was primarily treated with Pracchan karma, Siro lepa and Samana chikista for 4 months. Her symptoms got subsided after the treatment and further she didn’t had any other complaint even after 1year of follow up. Thus the Ayurvedic management protocol showed significant outcome and promising positive result.